2023
DOI: 10.3389/fvets.2023.1122092
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors analysis of Neospora caninum and Toxoplasma gondii in cattle of Beheira, Egypt

Abstract: IntroductionNeospora caninum and Toxoplasma gondii are closely related obligate intracellular protozoan parasites. They are considered to be the major causes of infectious abortions and congenital abnormalities in livestock worldwide resulting in huge economic losses. Currently, there are no reports on the prevalence of neosporosis or toxoplasmosis in cattle in Beheira, Egypt's most important region for cattle industry.MethodsThe current study investigated the presence of anti-N. caninum and anti-T. gondii ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Neospora caninum infection in Egyptian animals is underestimated, with a few seroprevalence reports in cattle, buffaloes, sheep, goats, camels, dogs, and cats, as well as limited information on clinical neosporosis. In our previous reports using the same ELISA as in the current study, we demonstrated seroprevalence rates for N. caninum of 3.9% in camels [44], 15.5% and 5% in sheep and goats, respectively [45], 5.8% in dogs, 3.4% in cats [49], and 24.6% in cattle [50]. Nonetheless, serum samples from aborted cows revealed N. caninum infections in addition to Coxiella burnetii [51] or Bovine Viral Diarrhoea Virus [52].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Neospora caninum infection in Egyptian animals is underestimated, with a few seroprevalence reports in cattle, buffaloes, sheep, goats, camels, dogs, and cats, as well as limited information on clinical neosporosis. In our previous reports using the same ELISA as in the current study, we demonstrated seroprevalence rates for N. caninum of 3.9% in camels [44], 15.5% and 5% in sheep and goats, respectively [45], 5.8% in dogs, 3.4% in cats [49], and 24.6% in cattle [50]. Nonetheless, serum samples from aborted cows revealed N. caninum infections in addition to Coxiella burnetii [51] or Bovine Viral Diarrhoea Virus [52].…”
Section: Discussionsupporting
confidence: 80%
“…Although N. caninum might not be a serious parasite for the pig industry, its detection in pigs might constitute a major risk for ruminants and other animals because of multiple species being raised in the same place. The seroprevalence in pigs was most similar to rates reported in cattle (24.6% [ 50 ], 29% [ 51 ], and 30.2% [ 52 ]) and higher than the rates reported in all other animal species, with the exception of one study in buffaloes ( Table 5 ). Furthermore, in comparison with the seroprevalence rate of N. caninum in domestic pigs from other countries, our infection rate seemed higher.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first seroepidemiological study evaluating jointly co-exposure of the three tested reproductive pathogens in different domestic ruminant species in Egypt. Metwally et al ( 23 ) detected 1.9% (7/358) of T. gondii and N. caninum co-exposure in cattle in Beheira governorate in Lower Egypt. Similarly, Aboelwafa et al ( 29 ) reported a co-exposure rate of 4.3% (4/92) of T. gondii and N. caninum in sheep in Luxor, Upper Egypt.…”
Section: Discussionmentioning
confidence: 99%